Treatment of relapsed Wilms tumour (WT) patients: Experience with topotecan. A report from the SIOP Renal Tumour Study Group (RTSG). Issue 4 (29th December 2014) - Mavinkurve‐Groothuis, A. M. C.; van den Heuvel‐Eibrink, M. M.; Tytgat, G. A.; van Tinteren, H.; Vujanic, G.; Pritchard‐Jones, K. L. P.; Howell, L.; Graf, N.; Bergeron, C.; Acha, T.; Catania, S.; Spreafico, F.
<x xml:space="preserve">Abstract</x> Background Topotecan has been variably incorporated in the treatment of patients with relapsed Wilms tumour (WT) who failed initial treatment with three or more effective drugs. Our objective was to describe outcome and to retrospectively investigate the potential role of topotecan in relapsed WT patients. Methods Children who were treated with topotecan as part of their chemotherapeutic regimens for relapsed WT were identified and included in our retrospective study. Patient charts were reviewed for general patient characteristics, histology and stage at initial diagnosis, number and type of relapse, salvage treatment schedules, toxicity, response to treatment and outcome. Results From 2000 to 2012, 30 children (median age at relapse 5.5 years, range 1.6–14.5 years) were identified to have received topotecan as part of their salvage regimens (primary progressive disease n = 3, first, second and third relapse n = 13, 9 and 2 respectively, partial response n = 3). Topotecan was administered as a single agent (12 patients) or in combination with other drugs (18 patients). Sixteen patients had high‐risk histology according to the SIOP classification, 15 died within 12 months because of progressive disease. Fourteen patients had SIOP intermediate‐risk histology of which four patients displayed objective responses to topotecan. Overall, 6 out of 14 intermediate‐risk patients survived (median follow up of 6 years), however, three of whom (stage V) had bilateral nephrectomy after topotecan treatment. Conclusions Topotecan does not seem to show effectiveness in the treatment of relapsed WT patients with initial high‐risk histology. In patients with intermediate‐risk histology, the role of topotecan might deserve further attention, to prove its efficacy. Pediatr Blood Cancer 2015;62:598–602. © 2014 Wiley Periodicals, Inc.